Locus of control: Concept development and operationalization - Oros, Laura (Revista de Psicología, 2005)
lResearch on the concept of locus of control began many years ago. Its importance stems from its relevance as an important coping resource as well as a predictive factor of other attitudinal, emotional and behavioural variables. Over the years the understanding of locus of control has improved and better ways of measuring this construct have emerged. Even though earlier on in history it was considered one– dimensional, currently there are at least six different dimensions which make up this construct. The following article invites the reader to review the history of the concept of locus of control, beginning with the first efforts at conceptualizing it. Furthermore, the author highlights some of the findings which today allow us to view locus of control from a multidimensional perspective.